Fine-scale species distribution modelling and genotyping by sequencing to examine hybridisation between two narrow endemic plant species - Ball, J.W.; Robinson, Todd; Wardell-Johnson, Grant; Bovill, J.; Byrne, M.; Nevill, Paul (NATURE PORTFOLIO, 2020)
Hybridization has an important and often positive role in plant evolution. However, it can also have negative consequences for species. Two closely related species of Ornduffia are endemic to the Porongurup Range in the South West Australian Global Biodiversity Hotspot. The rare Ornduffia calthifolia is found exclusively on the summits, while O. marchantii is more widely dispersed across a greater range of elevation and is not considered threatened. Hybridisation in suitable overlapping habitat has been suspected between them for decades. Here we combine genotyping by sequencing to verify hybridisation genetically, and fine scale (2 m resolution) species distribution modelling (SDM) to test if hybrids occur in suitable intersecting habitat. From a study area of c. 4700 ha, SDM identified c. 275 ha and c. 322 ha of suitable habitat for O. calthifolia and O. marchantii, respectively. We identified range overlap between species of c. 59 ha), which enveloped 32 individuals confirmed to be hybrids. While the hybrids were at the margin of suitable habitat for O. marchantii, their preference for elevated habitat was closer to the more narrowly distributed O. calthifolia. The combination of genetic data and fine scale spatial modelling approaches enabled a better understanding of hybridisation among taxa of conservation significance. However, the level to which hybrid proliferation and competition for habitat presents as a threat to O. calthifolia is currently unknown and requires priority in conservation management given the threats from global warming and disturbance by tourism.